Side Effects and Determinant of the Use of 3-Month Contraceptive Injection - Priyanti, Sari; Syalfina, Agustin Dwi (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Acceptor of contraceptive injection increased from 11.7% to 27.8% since 2010-2013. Contraceptive injection of Depo Medroxy Progesterone Acetate (DMPA) is given every 3 months by intramuscular. The long-term use of 3-month contraceptive injetion for more than two years can cause side effects such as menstrual disorders and decreased libido due to accumulation of progesterone hormone in the body that suppressed estrogen effect. This study aimed to analyze the association in long-term use of 3-month contraceptive injetion with menstrual disorders and decreased libido in Puskesmas (Primary health care) Puri, Mojokerto Regency in 2016. The study was observational analytics with cross sectional approach with sample 73 contraceptive acceptors. The data were analyzed by using univariate, bivariate and multivariate analysis with logistic regression and multivariate general model. The results showed that the duration of use of 3-month contraceptive injetion was significant with side effect of menstrual disorders (PR=0.142; 95%CI: 0.040-0.502) and decreased libido (PR=0.275; 95%CI: 0.100-0.756). Conclusion: menstrual disorders and decreased libido associated with the duration of use of 3-month contraceptive injetion.